Quantitative summer-temperature reconstructions for the last 2000 years based on pollen-stratigraphical data from northern Fennoscandia - Bjune, AE; Seppa, H; Birks, HJB (SPRINGER, 2009)
Quantitative reconstructions of mean July temperatures (T (jul)) based on new and previously published pollen-stratigraphical data covering the last 2000 years from 11 lakes in northern Fennoscandia and the Kola Peninsula are presented. T (jul) values are based on a previously published pollen-climate transfer function for the region with a root-mean-square error of prediction (RMSEP) of 0.99A degrees C. The most obvious trend in the inferred temperatures from all sites is the general decrease in T (jul) during the last 2000 years. Pollen-inferred T (jul) values on average 0.18 +/- A 0.56A degrees C (n = 91) higher than present (where "present" refers to the last three decades based on pollen-inferred T (jul) in core-top samples) are indicated between 0 and 1100 AD (2000-850 cal year BP), and temperatures -0.2 +/- A 0.47A degrees C (n = 78) below present are inferred between 1100 and 1900 AD (850-50 cal year BP). No consistent temperature peak is observed during the 'Medieval Warm Period', ca. 900-1200 AD (1100-750 cal year BP), but the cooler period between 1100 and 1900 AD (850-50 cal year BP) corresponds in general with the 'Little Ice Age' (LIA). Consistently with independent stable isotopic data, the composite pollen-based record suggests that the coldest periods of the LIA date to 1500-1600 AD (450-350 cal year BP) and 1800-1850 AD (150-100 cal year BP). An abrupt warming occurred at about 1900 AD and the twentieth century is the warmest century since about 1000 AD (950 cal year BP).